“KA’EN KELUN BA MALU” IN DISTRIBUTION OF CULTURE AND LEVEL OF COMMUNITY PARTICIPATION - Imelda Nahak (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2019)
Community participation is very important and contributes to the effectiveness of the resulting development planning. However, until now community participation has not been realized ideally. Previous studies have offered various efforts to increase community participation, namely increased local community initiatives (Muhlinghaus & Walty, 2001), development of government and community cooperation (Pandey & Miznikov, 2001), integration of art and planning (Burford, Kissmann, Rosado- May, Dzul, & Harder, 2012), optimizing the role of social capital (Cerar, 2014), socialization to the bottom of the community (Defina, 2012), participatory leadership (Alyas, 2015), allocation of village funds (Atmojo, Eko, Fridayani, Kasiwi, & Pratama, 2017) and optimizing the role of young people as mobilizers (Fitriani, Selinaswati, & Mardiah, 2017). Unfortunately, there has not been an assessment effort that looks at the cultural side. This qualitative case study examines efforts to increase community participation by considering cultural factors that can contribute to the effectiveness of development planning at the village level. Data obtained through in-depth interviews, participant observation and documentation. This study found that the culture factor of mamfatin ukunrai could inhibit community participation in Naran Village. The community believes that planning development is the duty of the government so that it should not actively participate in planning meetings. Therefore, the researcher offers a model of the family code as an effort to reduce the impact of the culture. Ka'en kelun ba ashamed to represent the government's invitation to cooperate with the community for the realization of development from the ground level.